Main directions of development of the economy of Kazakhstan education in modern times. (Journal of Economic Research & Business Administration, 2015)
In the modern period the main task before the people – getting a decent education . Since independence in our country, a kardionalnye transformation in the education system. This is due primarily to the sustainable socio-economic development of the country, which requires further development of the education sector. Challenges faced by our country to the level of developed countries, require increasing the competitiveness of young professionals, their ability to meet the challenges of modern times. The current generation – future professionals capable distant future is to solve the problem further development of the country. On this basis, to provide training modern specialists should further develop the education sector, which serve as the main order of the day.
Keywords: education system; indicators of education; research and technological development; the strategic goals of education and science sectors; competitiveness